Design of a novel bioink suitable for the 3D printing of lymphoid cells - Ribezzi, Davide; Pinos, Riccardo; Bonetti, Lorenzo; Cellani, Marco; Barbaglio, Federica; Scielzo, Cristina; Farè, Silvia (Frontiers in Biomaterials Science, 2023)
For decades, in vitro 2D cell culture techniques have been employed in research, but they fail to recapitulate the complexity of natural tissues. 3D bioprinting could potentially overcome this drawback due to the possibility to control the spatial disposition of living cells and the geometry of the 3D scaffold. This study reports the design and characterization of a novel bioink for extrusion bioprinting, analyzing different blend formulations composed of alginate, gelatin, and methylcellulose, suitable as cell-laden bioink for lymphoid cells, in particular those isolated from patients with Chronic Lymphocytic Leukemia (CLL). The rheological properties as a function of temperature and the printability of the formulations were investigated to define the optimal printing parameters. In vitro stability of printed scaffolds was investigated under culture conditions and compression tests were performed on printed and bioprinted scaffolds to compare their mechanical properties with those of fresh lymphoid tissue. Finally, MEC1, a CLL cell line, was bioprinted to investigate cell viability, cell density, and cell capability to be released from the scaffold over time. Results showed that, for the selected blends, good shape fidelity and printing accuracy were achieved with a limitation on the number of printed layers. Scaffolds withstood culture conditions showing stability for up to three weeks and their mechanical properties were similar to the ones of lymphoid tissues already reported in the literature. High cell viability after 21 days was observed for both MEC1 and primary peripheral mononuclear cells, confirming the possibility to use the selected formulation to successfully bioprint lymphoid cells by possibly mimicking their native lymphoid microenvironment.